외국인근로자 고용정책변동에 따른 사회통합정책대상으로의 포용 가능성 탐색: 단기순환원칙의 고용정책을 중심으로 - 정명주; Chung Myungju; 김소윤; Kim Soyoon (한국거버넌스학회보, 2020)
한국사회가 외국인 유입으로 다문화적 상황으로 전개되면서 정부는 다문화정책 관련 다양한 제도적 장치와 정책을 추진하였다. 이러한 정책의 일환으로 2004년 고용허가제를 도입하면서 한국에 외국인근로자가 본격적으로 유입되었다. 도입당시 외국인근로자에 대한 고용정책적 관점은 단기순환원칙에 입각하여 정주화를 금지하는 것을 정책적 기조로 내세웠다. 한편 사회통합정책적 관점에서는 장기적으로 우리사회 이민자라는 인식하에 결혼이민자에 집중하였고 외국인근로자는 배제되는 경향을 보였다. 그러나 시간이 지나면서 단기순환을 원칙으로 하는 고용정책내용이 몇 차례의 변동을 겪게 되었고 그에 따라 외국인근로자의 체류양태 또한 변화하고 있다. 본 연구의 목적은 고용허가제가 도입된 이후 고용정책내용이 단기순환적 관점에서 어떠한 변화를 가져왔고, 그에 따라 외국인근로자의 체류양태가 어떻게 변화되고 있는가를 분석하여 사회통합정책적 관점에서 외국인근로자를 우리사회 통합의 대상으로 포용할 수 있는 가능성을 탐색하고자 하였다. 분석 결과 몇 차례의 고용정책내용이 단기순환의 원칙에 위배되는 방향으로 전개되어 왔고, 이에 따라 외국인근로자의 체류양태 또한 그 규모는 확대되고 장기체류화하고 있는 경향이 뚜렷이 드러나고 있는 것으로 분석되었다. 그럼에도 불구하고 사회통합정책적 관점에서는 여전히 미흡한 수준에 머물러 있는 것으로 나타났다. 따라서 이러한 결과를 토대로 다문화적 상황이 성숙되어 가는 과정에서 외국인근로자에 대해 사회통합정책적 관점에서 보다 적극적 포용대상으로 제도와 정책의 전환이 필요한 때임을 제안하였다. As Korean society developed into a multicultural situation due to the influx of foreigners, the government promoted various institutional devices and policies related to multicultural policy. As part of this policy, the introduction of the employment permit system in 2004 brought foreign workers to Korea in earnest. At the time of introduction, the perspective of the employment policy on foreign workers was to prohibit settlement based on the principle of short-term circulation. On the other hand, from the perspective of social cooperation policy, they focused on marriage immigrants in the long term as being immigrants in our society, and foreign workers tended to be excluded. However, over time, the short-term employment policy has undergone several fluctuations, and as a result, the type of stay of foreign workers has changed. The purpose of this study is to analyze how changes in the employment policy have been made in the short-term cyclical view since the introduction of the employment permit system, and how the status of stay of foreign workers has changed accordingly. We attempted to explore the possibilities for inclusion as an object of integration. As a result of the analysis, several employment policy contents have been developed in a direction that violates the principle of short-term circulation. As a result, the trend of staying in foreign workers is also increasing and the trend of long-term stay becomes clear. Nevertheless, the level of social cooperation policy remains low. Therefore, based on these results, we suggested that it is time for foreign workers to change their systems and policies to be more actively embraced from a social cooperation policy perspective.